2011
DOI: 10.1016/j.brainres.2010.11.075
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic mechanisms of lateral parabrachial nucleus facilitate sodium depletion-induced NaCl intake

Abstract: Purinergic receptors are present in the lateral parabrachial nucleus (LPBN), a pontine structure involved in the control of sodium intake. In the present study, we investigated the effects of α,β-methyleneadenosine 5'-triphosphate (α,β-methylene ATP, selective P2X purinergic agonist) alone or combined with pyridoxalphosphate-6-azophenyl-2',4'-disulfonic acid (PPADS, P2X purinergic antagonist) or suramin (non-selective P2 purinergic antagonist) injected into the LPBN on sodium depletion-induced 1.8% NaCl intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Signals that influence water and NaCl intake like those from arterial baroreceptors, cardiopulmonary receptors, gustatory receptors and other visceral receptors that reach the NTS ascend to the LPBN (Norgren, 1981;Lança and van der Kooy, 1985;Ciriello et al, 1984;Fulwiler and Saper, 1984;Herbert et al 1990;Jhamandas et al, 1992Jhamandas et al, , 1996. These signals may modulate the activity of LPBN inhibitory mechanisms by releasing different neurotransmitters like serotonin, cholecystokinin, corticotrophin-releasing factor (CRF) and glutamate which increase the inhibitory action, whereas others like GABA, opioids, ATP and noradrenaline reduce the inhibitory action (Andrade et al, 2004Callera et al, 2005;De Gobbi et al, 2009, Gasparini et al, 2009, De Oliveira et al, 2007, 2008Menezes et al, 2011Menezes et al, , 2014Roncari et al, 2014). The deactivation of the inhibitory mechanisms by changing the activity of specific neurotransmitters/receptors in the LPBN increases hypertonic NaCl and/ or water intake induced by different dipsogenic or natriorexigenic stimuli like angiotensin II (ANG II), sodium depletion, water deprivation, central cholinergic activation or even osmoreceptor activation Johnson, 1995, 1998;Menani et al, 1996Menani et al, , 2002Menani et al, , 2014De Luca et al, 2003;Andrade et al, 2004Andrade et al, , 2006De Gobbi et al, 2009;Gasparini et al, 2015b).…”
Section: Introductionmentioning
confidence: 97%
“…Signals that influence water and NaCl intake like those from arterial baroreceptors, cardiopulmonary receptors, gustatory receptors and other visceral receptors that reach the NTS ascend to the LPBN (Norgren, 1981;Lança and van der Kooy, 1985;Ciriello et al, 1984;Fulwiler and Saper, 1984;Herbert et al 1990;Jhamandas et al, 1992Jhamandas et al, , 1996. These signals may modulate the activity of LPBN inhibitory mechanisms by releasing different neurotransmitters like serotonin, cholecystokinin, corticotrophin-releasing factor (CRF) and glutamate which increase the inhibitory action, whereas others like GABA, opioids, ATP and noradrenaline reduce the inhibitory action (Andrade et al, 2004Callera et al, 2005;De Gobbi et al, 2009, Gasparini et al, 2009, De Oliveira et al, 2007, 2008Menezes et al, 2011Menezes et al, , 2014Roncari et al, 2014). The deactivation of the inhibitory mechanisms by changing the activity of specific neurotransmitters/receptors in the LPBN increases hypertonic NaCl and/ or water intake induced by different dipsogenic or natriorexigenic stimuli like angiotensin II (ANG II), sodium depletion, water deprivation, central cholinergic activation or even osmoreceptor activation Johnson, 1995, 1998;Menani et al, 1996Menani et al, , 2002Menani et al, , 2014De Luca et al, 2003;Andrade et al, 2004Andrade et al, , 2006De Gobbi et al, 2009;Gasparini et al, 2015b).…”
Section: Introductionmentioning
confidence: 97%
“…Studies that have investigated the involvement of the LPBN in the control of fluid-electrolyte balance demonstrated that different neurotransmitters like serotonin, cholecystokinin, glutamate and corticotrophin releasing factor (CRF) or receptors like ␣ 2 -adrenoceptors, GABAergic, opioid or purinergic receptors in the LPBN are involved with the control of sodium intake [1,3,5,[18][19][20][21][22][23][24][25][26][27][28]. The activation of the ␣ 2 -adrenoceptors with bilateral injections of noradrenaline or moxonidine into the LPBN increases 0.3 M NaCl and water intake induced by the treatment with the diuretic furosemide (FURO) combined with low dose of the angiotensin converting enzyme inhibitor captopril (CAP) injected subcutaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Important inhibitory mechanisms for the control of sodium and water intake are present in the lateral parabrachial nucleus (LPBN) (De Gobbi et al, 2009;Gasparini et al, 2009;De Oliveira et al, 2011;Menezes et al, 2011;Menani et al, 2014). The LPBN receives ascending projections from the medial portion of the nucleus of the solitary tract (mNTS), the site of the first synapse of the afferents from arterial baroreceptors, cardiopulmonary receptors, gustatory receptors and other visceral receptors that influence water and NaCl intake (Norgren, 1981;Lanca and van der Kooy, 1985;Herbert et al, 1990;Thunhorst, 1997, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…The LPBN receives ascending projections from the medial portion of the nucleus of the solitary tract (mNTS), the site of the first synapse of the afferents from arterial baroreceptors, cardiopulmonary receptors, gustatory receptors and other visceral receptors that influence water and NaCl intake (Norgren, 1981;Lanca and van der Kooy, 1985;Herbert et al, 1990;Thunhorst, 1997, 2007). These signals may modulate the activity of LPBN inhibitory mechanisms by releasing different neurotransmitters like serotonin, cholecystokinin (CCK), corticotrophinreleasing factor (CRF) and glutamate which are those that increase the inhibitory action, whereas others like GABA, opioids, ATP and noradrenaline (NOR) reduce the inhibitory action (De Gobbi et al, 2009;Gasparini et al, 2009;De Oliveira et al, 2011;Menezes et al, 2011;Menani et al, 2014). The deactivation of the inhibitory mechanisms by changing the activity of specific neurotransmitters/receptors in the LPBN increases hypertonic NaCl and/or water intake induced by different dipsogenic or natriorexigenic stimuli like angiotensin II (ANG II), sodium depletion, water deprivation, central cholinergic activation or even osmoreceptor activation Johnson, 1995, 1998;Menani et al, 1996bMenani et al, , 2002De Luca et al, 2003;Andrade et al, 2004Andrade et al, , 2006De Gobbi et al, 2009;Almeida et al, 2011).…”
Section: Introductionmentioning
confidence: 99%